2014
DOI: 10.3389/fphar.2014.00099
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration with brain iron accumulation: update on pathogenic mechanisms

Abstract: Perturbation of iron distribution is observed in many neurodegenerative disorders, including Alzheimer's and Parkinson's disease, but the comprehension of the metal role in the development and progression of such disorders is still very limited.The combination of more powerful brain imaging techniques and faster genomic DNA sequencing procedures has allowed the description of a set of genetic disorders characterized by a constant and often early accumulation of iron in specific brain regions and the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 177 publications
3
129
1
1
Order By: Relevance
“…Although various factors other than iron content also affect the estimated iron concentration in the brain on MRI, MRI is used to diagnose many kinds of iron-storage diseases, such as neurodegeneration with brain iron accumulation (NBIA) [65][66][67][68], Alzheimer's disease [69,70], Parkinson's disease [71,72], multiple sclerosis [73,74], Friedreich's ataxia [75,76], and Huntington's disease [53,77]. NBIA is a group of neurodegenerative diseases characterized by iron accumulation in the basal ganglia.…”
Section: Ironmentioning
confidence: 99%
“…Although various factors other than iron content also affect the estimated iron concentration in the brain on MRI, MRI is used to diagnose many kinds of iron-storage diseases, such as neurodegeneration with brain iron accumulation (NBIA) [65][66][67][68], Alzheimer's disease [69,70], Parkinson's disease [71,72], multiple sclerosis [73,74], Friedreich's ataxia [75,76], and Huntington's disease [53,77]. NBIA is a group of neurodegenerative diseases characterized by iron accumulation in the basal ganglia.…”
Section: Ironmentioning
confidence: 99%
“…The incubation of ferritin with H 2 O 2 (Liu and Hu 2009), salsolinol (Kang 2009) or methylglyoxal and lysine (An and Kang 2013) caused oxidative DNA damage, and this was prevented by iron chelators. Furthermore the presence of mutant L ferritin with a perturbed COOH-terminal structure as observed in neuroferritinopathy patients leads to excess LIP and ROS generation (see also below) (Levi and Finazzi 2014). It is thus possible that, in specific chemical or genetic conditions, iron release from ferritin may be toxic to cells and tissues and contribute to the pathology.…”
Section: Mammalian Ferritin Structurementioning
confidence: 99%
“…The most paradigmatic example is Neuroferritinopathy (OMIM, 606159), an autosomal dominant neurodegenerative disorder due to mutations in the FtL gene and mainly characterized by extrapyramidal symptoms (McNeill and Chinnery 2012;Levi and Finazzi 2014). Magnetic resonance imaging reveals signs of cerebral iron accumulation, particularly in the basal ganglia (Crompton et al), and the histopathology confirmed the iron accumulation together with the presence of ferritin aggregates, with a nuclear or cytosolic localization, in neurons and glial cells; serum ferritin is often decreased (McNeill and Chinnery 2012).…”
Section: Ferritin Mutations In Genetic Disordersmentioning
confidence: 99%
See 2 more Smart Citations